Key factors for building information modelling implementation in the context of environmental, social, and governance and sustainable development goals integration: a systematic literature review - Jing, Wu; Alias, Aidi Hizami (Multidisciplinary Digital Publishing Institute, 2024)
Driven by global sustainability trends, Building Information Modelling (BIM) technology is increasingly becoming a key tool in the construction industry to improve efficiency and sustainability. This study aims to identify the key factors affecting BIM implementation in the context of Environmental, Social, and Governance (ESG) and Sustainable Development Goals (SDGs) and to construct a theoretical framework for BIM implementation based on these factors. To achieve this objective, this study used a systematic literature review (SLR) method to systematically review the relevant literature between 2009 and 2024 and identified 16 key factors from the selected 406 studies through keyword co-occurrence analysis (using VOSviewer 1.6.20) and data coding. These key factors include top management support for ESG and SDGs, alignment of SDGs, ESG integration, technical support, BIM software, BIM hardware, structural adjustment and collaboration, capacity building, change management, skill and attitude, educational training and development, incentive mechanism, roles and responsibilities, sustainable construction practices, policies and regulations, and resource efficiency. This study categorises these factors under the Strategy, Technology, Organisation, People, Environment (STOPE) framework and proposes a theoretical implementation framework for BIM accordingly. The findings not only provide a practical guiding framework for the sustainable development of construction companies in the context of ESG and SDG integration but also lay a solid theoretical foundation for future empirical research. © 2024 by the authors.